Trypanosomosis of livestock in India: A review of two decades - PATHAK, K M L; CHHABRA, M B (The Indian Journal of Animal Sciences, 2011)
Trypanosomosis ranks as the most important haemoprotozoan disease impacting the livestock economy in India through widespread morbidity and mortality. Although prevalent in almost all parts of the country, data from different states showed wide variations being influenced by various epidemiological factors. During the last two decades, outbreaks as well as individual cases involving bovines, equids, camels, dogs and some wild animals have been reported. Endemicity appears to have extended to new areas. Reported clinico-haematological changes cover a vast range and vary between the host species, even as progressive emaciation, anaemia and intermittent fever appear to be more common. Diagnostic techniques have undergone major improvements due to availability of purified antigens and the developments in molecular biology with application in parasitic infections. Standardization of some tests and emergence of assays has led to more reliable epidemiological data being generated. DNA-based technologies have enabled the characterization of antigenic components of trypanosomes. Chemotherapy and availability of drugs have witnessed only limited progress. Control strategies do not seem to take into account the vector component. There is need for greater coordination among laboratory workers and field personnel to take stock of the present status and also to define the priority areas for research with the objective of minimizing the ongoing losses.